Limited Support for Thyroid Hormone or Corticosterone Related Gene Expression as a Proximate Mechanism of Incubation Temperature-Dependent Phenotypes in Birds - Hope, Sydney F.; Buenaventura, Christopher R.; Husain, Zahabiya; DuRant, Sarah E.; Kennamer, Robert A.; Hopkins, William A.; Thompson, Christopher K. (Frontiers in Physiology, 2019)
The conditions that animals experience during early development can have profound consequences for health and fitness. In birds, one of the most important aspects of development is egg incubation temperature. A small decrease in average temperature leads to various impacts on offspring phenotype, such as smaller body sizes, slower growth rates, and less efficient metabolic activity. Little is known, however, about the proximate mechanisms underlying these incubation temperature-induced phenotypic changes. Two important hormones which could play a proximate role are thyroid hormone and corticosterone, which mobilize stored energy reserves and coordinate the normal growth of tissues, particularly in the brain. Previous research shows that circulating blood concentrations of both hormones are influenced by incubation temperature, but the mechanism by which incubation temperature may lead to these changes is unknown. We hypothesized that incubation temperature induces changes in thyroid hormone and corticosterone regulation, leading to changes in expression of hormone-sensitive genes in the brain. To test this, we incubated wood duck (Aix sponsa) eggs at three different temperatures within the natural range (35.0, 35.8, and 37.0C). We measured mRNA expression of thyroid hormone-related neuroendocrine endpoints (deiodinase 2/3, thyroid hormone receptor /, neural regeneration related protein, and Krueppel-like factor 9) in newly hatched ducklings and corticosterone-related neuroendocrine endpoints (mineralocorticoid receptor, glucocorticoid receptor, cholecystokinin, and brain-derived neurotrophic factor) in 15 day-old ducklings using qPCR on brain tissue from the hippocampus and hypothalamus. Contrary to our predictions, we found that mRNA expression of thyroid hormone-related endpoints in both brain areas were largely unaffected by incubation temperature, although there was a trend for an inverse relationship between mRNA expression and incubation temperature for several genes in the hypothalamus. We also found that mineralocorticoid receptor mRNA expression in the hypothalamus was lower in ducklings incubated at the low relative to the high temperatures. This study is the first to evaluate the effects of incubation temperature on mRNA expression of neuroendocrine endpoints in the developing avian brain and suggests that these particular endpoints may be largely resistant to changes in incubation temperature. Thus, further research into the proximate mechanisms for incubation temperature-induced developmental plasticity is needed.